Perancangan Dan Implementasi Strategi Pemasaran Dengan Mengintegrasikan Media Instagram Dan Youtube Sebagai Platform Pemasaran Twinkle_Olshop Batam Official - Elfan Wahyu Mulyana; Emelly Emelly (Universitas Internasional Batam, 2021)
Twinkle_Olshop Batam Official is a business that sells various kinds of household items and decorative items. The problem faced by Twinkle_Olshop Batam Official lies in its marketing strategy. To overcome this problem, a digital marketing strategy was designed that aims to increase the marketing of Twinkle_Olshop Batam Official. The marketing strategy used is to create Instagram accounts and also videos about the products offered which will be shared on YouTube accounts. The research method used consists of seven stages, namely observation, problem identification, problem formulation, implementation, design, process analysis, and evaluation. The marketing strategy proposed to partners is relatively simple so that it is easy to implement. And if the partners continue to carry out the marketing strategy that has been proposed, of course it will increase the distribution range of partners products to be wider.